POLA PENDIDIKAN KARAKTER PADA BOARDING SCHOOL DI SMA ISLAM ABDURRAB KOTA PEKANBARU - Nasution, Nurhajjah; ayub, Daeng; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Character education is interpreted as value education, moral education, which encourages students' abilities. The formulation of the problem in this research is how high is the value of student character education on boarding schools in Abdurrab Islamic High School, Pekanbaru City and how big is the contribution of character education to the boarding school in Abdurrab Islamic High School, Pekanbaru City. The benefit of this study is to determine the level of character education of students on boarding schools in Abdurrab Islamic High School, Pekanbaru City. Found the contribution of character education to the boarding school at Abdurrab Islamic High School in Pekanbaru City. The population in this study were all students who were boarding schools in Abdurrab Islamic High School, Pekanbaru, amounting to 65 respondents. The sampling technique in this study is using a simple random sampling technique. It is said to be simple (simple) because the taking of sample members from the population is done randomly regardless of the strata that exist in the population. The instrument in this study is a questionnaire or questionnaire containing statements about the pattern of character education on boarding schools in Abdurrab Islamic High School, Pekanbaru City with indicators 1) Religious, 2) Nationalists 3) Mandiri 4) Mutual cooperation 5) Integrity. Religious mean with mean 4.32 and SD 0.38 then Nationalist with mean 3.96 and SD 0.38, then independent indicators with mean 4.04 and SD 0.39, then mutual cooperation with mean 4.16 and SD 0.52, then integrity with a mean of 4.04 and SD 0.39. The meaning is a low nationalist indicator for boarding school students in Abdurrab Islamic High School, Pekanbaru City. However, the value of religious character is very high for boarding school students in Abdurrab Islamic High School, Pekanbaru City.Key Words: Pattern of Education, Character, Boarding School